Stres sebagai moderator ke atas hubungan antara gaya kepimpinan ketua dengan tingkah laku buli - Mohd. Halim, Hairul Akmal (2014)
The purpose of this study is to identify the effect of stress to moderate the relationship between leader’s leadership styles and workplace bullying in Malacca Municipal Councils. A total of 118 leaders from Malacca Municipal Councils have been chosen as the respondents for this study. The data are collected by using a set of questionnaire which consists of four parts namely part A (Demography), part B (leadership styles), part C (stress sources), and part D (bullying). The measurement tools used for data collection included Path Goal Theory Questionnaire, Administrative Stress Index (ASI) and Negative Act Questionnaire (NAQ). Then, the collected data was analyzed by using descriptive (mean and percentages) and inferential statistic (multiple linear regression and hierarchical regression). Data were analyzed using “Statistical package for Social Science” version 19.0. The findings reveal that the most leadership style being used is democratic and stress is at a moderate level. Besides, the results also show that there is a significant effect of leader’s leadership styles on workplace bullying in Malacca Municipal Councils. The result also demonstrates that stress does not a moderator to the relationship between leader’s leadership styles on workplace bullying. Lastly, some suggestions have been given to future researcher.